2005
DOI: 10.1099/mic.0.27566-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the quorum-sensing regulatory protein LasR is strongly affected by iron and oxygen concentrations in cultures of Pseudomonas aeruginosa irrespective of cell density

Abstract: Expression of the quorum-sensing regulatory protein LasR is strongly affected by iron and oxygen concentrations in cultures of Pseudomonas aeruginosa irrespective of cell density The expression of the transcriptional regulatory protein LasR, a main component of the quorum-sensing (QS) system in Pseudomonas aeruginosa, was recently found to be sensitive to several environmental factors in addition to its dependency on cell density. However, the inherent effects of the different factors have seldom been separate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 52 publications
3
55
0
Order By: Relevance
“…Quorum sensing is mainly dependent on cell density. However, it has been demonstrated that quorum sensing is not only cell-densitydependent, but is also influenced by the presence of iron and/or oxygen (Bollinger et al, 2001;Kim et al, 2005). This could explain the observations in our study related to pyoverdine utilization and growth in the presence of oxidizing compounds, which was possible only at high inoculum sizes (Vinckx et al, 2008).…”
Section: Introductionsupporting
confidence: 46%
“…Quorum sensing is mainly dependent on cell density. However, it has been demonstrated that quorum sensing is not only cell-densitydependent, but is also influenced by the presence of iron and/or oxygen (Bollinger et al, 2001;Kim et al, 2005). This could explain the observations in our study related to pyoverdine utilization and growth in the presence of oxidizing compounds, which was possible only at high inoculum sizes (Vinckx et al, 2008).…”
Section: Introductionsupporting
confidence: 46%
“…However, the production of these secondary metabolites also seems to be dependent on environmental cues (3,62). A link between QS and iron homeostasis was suggested previously (5,11,21,24,25,52,60). Moreover, PQS was shown to exhibit an iron-chelating activity, and PQS-dependent rhlR induction seems to be at least in part a consequence of iron depletion (6).…”
mentioning
confidence: 99%
“…Controlled expression of several key P. aeruginosa virulence factors, including elastase (lasB) (Pearson et al, 1997), exotoxin A , type II secretory pathway proteins (xcp) (Chapon-Hervé et al, 1997) and pyoverdine (Kim et al, 2005;Stintzi et al, 1998) are mediated by population density bio-sensor mechanisms, a process known as quorum sensing. P. aeruginosa has two quorum-sensing systems, the Las and Rhl systems, each influencing the expression of a range of virulence factors (Passador et al, 1993;Pearson et al, 1994).…”
Section: Introductionmentioning
confidence: 99%